Isolation and characterization of tannins tolerant bacteria from rumen fluid of free ranging sheep and goats - Kebede, M.; Odenyo, A.A.; Assefa, F. (2007)
Four straight rods and three spherical bacteria were isolated using roll tubes inoculated with rumen fluid from sheep and goats and enriched with tannic acid. The isolates were characterized by morphology, products of fermentation and restriction fragment length polymorphism that indicated the cocci isolates to be Streptococcus while the rods are closely related to recently isolated tannin tolerant bacteria within the Mebsiella genus. All of the isolates were able to grow in 30 gIL tannin extract of Acacia angustissima ground dry leaves except isolates EG 2.1 and EG 1 that grew in 20 g/L of tannic acid.